Relation between electrical and mechanical dyssynchrony in patients with left bundle branch block: An electro‐ and vectorcardiographic study. Issue 4 (18th December 2017) - De Pooter, Jan; El Haddad, Milad; Kamoen, Victor; Kallupurackal, Thomas Tibin; Stroobandt, Roland; De Buyzere, Marc; Timmermans, Frank
Abstract : Background: Current guidelines select patients for cardiac resynchronization therapy (CRT) mainly on electrocardiographic parameters like QRS duration and left bundle branch block (LBBB). However, among those LBBB patients, heterogeneity in mechanical dyssynchrony occurs and might be a reason for nonresponse to CRT. This study assesses the relation between electrocardiographic characteristics and presence of mechanical dyssynchrony among LBBB patients. Methods: The study included patients with true LBBB (including mid‐QRS notching) on standard 12‐lead electrocardiograms. Left bundle branch block‐induced mechanical dyssynchrony was assessed by the presence of septal flash on two‐dimensional echocardiography. Previously reported electro‐ and vectorcardiographic dyssynchrony markers were analyzed: global QRS duration (QRSDLBBB ), left ventricular activation time (QRSDLVAT ), time to intrinsicoid deflection (QRSDID ), and vectorcardiographic QRS areas in the 3D vector loop (QRSA3D ). Results: The study enrolled 545 LBBB patients. Septal flash (SF) is present in 52% of patients presenting with true LBBB. Patients with SF are more frequent female, have less ischemic heart disease and smaller left ventricular dimensions. In multivariate analysis longer QRSDLBBB, QRSDLVAT and larger QRSA3D were independently associated with SF. Of all parameters, QRSA3D has the best accuracy to predict SF, although overall accuracy remains moderate (59% sensitivity, 58% specificity). The predictive value of QRSA3D remained constant in both sexes, irrespective of ischemic heart disease, ejection fraction and even when categorizing for QRSDLBBB . Conclusion: In LBBB patients, large QRS areas correlate better with mechanical dyssynchrony compared to wide QRSD intervals. However, the overall accuracy to predict mechanical dyssynchrony by electrocardiographic dyssynchrony markers, even when using complex vectorcardiographic parameters, remains low.